Challenges and opportunities for policy decisions to address health equity in developing health systems: case study of the policy processes in the Indian state of Orissa - Gopalan Saji S; Mohanty Satyanarayan; Das Ashis (BMC, 2011)
Abstract Introduction Achieving health equity is a pertinent need of the developing health systems. Though policy process is crucial for planning and attaining health equity, the existing evidences on policy processes are scanty in this regard. This article explores the magnitude, determinants, challenges and prospects of 'health equity approach' in various health policy processes in the Indian State of Orissa - a setting comparable with many other developing health systems. Methods A case-study involving 'Walt-Gilson Policy Triangle' employed key-informant interviews and documentary reviews. Key informants (n = 34) were selected from the departments of Health and Family Welfare, Rural Development, and Women and Child Welfare, and civil societies. The documentary reviews involved various published and unpublished reports, policy pronouncements and articles on health equity in Orissa and similar settings. Results The 'health policy agenda' of Orissa was centered on 'health equity' envisaging affordable and equitable healthcare to all, integrated with public health interventions. However, the subsequent stages of policy process such as 'development, implementation and evaluation' experienced leakage in the equity approach. The impediment for a comprehensive approach towards health equity was the nexus among the national and state health priorities; role, agenda and capacity of actors involved; and existing constraints of the healthcare delivery system. Conclusion The health equity approach of policy processes was incomprehensive, often inadequately coordinated, and largely ignored the right blend of socio-medical determinants. A multi-sectoral, unified and integrated approach is required with technical, financial and managerial resources from different actors for a comprehensive 'health equity approach'. If carefully geared, the ongoing health sector reforms centered on sector-wide approaches, decentralization, communitization and involvement of non-state actors can substantially control existing inequalities through an optimally packaged equitable policy. The stakeholders involved in the policy processes need to be given orientation on the concept of health equity and its linkage with socio-economic development.